IOI Hair Salon Management System - Tan, Pei Yu; Hairulnizam Mahdin, (Applied Information Technology And Computer Science, 2023)
A mobile-based IOI Hair Salon Management System is developed to assist the owner and staff to manage the business-related information systematically since the current business workflow is implemented manually. The owner manually calculates the business sales in a logbook that may cause calculation errors, the appointment details are recorded in a record book and the latest service information is updated offline. This system aims to improve business management efficiency and simplify the appointment booking process. The waterfall development-based methodology is used to conduct the project. This system is developed as an Android-based mobile application using Firebase along with the Flutter framework and Dart language. An intuitive and user-friendly system is built, which has a short learning curve for users to use. Based on the User Acceptance Testing (UAT), most users, including customers, hair stylists and the owner are very satisfied with user interfaces and features of the developed system.